The Role of Fintech in Mediating the Influence of Financial Efficiency and Risk Perception on Investment Decisions in the Capital Market - Danang Setiawan, Riskal; Suhardi, S.; Astuti, Nelly; Sri Rejeki, Nadia (Golden Ratio of Finance Management, 2025)
This study analyzes the relationship between financial efficacy, the use of fintech services, investment decisions, and risk perception in the context of financial technology adoption and investment decision-making. The regression analysis results show that the model can explain variations in using fintech services and investment decisions. These findings suggest that although the model is relevant in explaining the factors that influence both variables, other external factors contribute to variation in individual financial decision-making. Path analysis shows financial efficacy positively and significantly influences fintech services and investment decisions. In addition, using fintech services also plays a role in encouraging investment decisions, with a path coefficient of the same size. Other findings suggest that risk perception has a positive relationship with fintech adoption, indicating that individuals with higher risk awareness are more likely to turn to fintech services to access more transparent and secure financial information. The implications of this study highlight the importance of financial education in increasing individual confidence in managing finances and the role of fintech in accelerating financial inclusion and investment participation. This research recommends strengthening digital financial literacy and developing policies that support the adoption of financial technology to increase the effectiveness of financial decision-making in the community.